2008
DOI: 10.1016/j.ijid.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enteritidis brain abscess in a sickle cell disease patient: case report and review of the literature

Abstract: S. enteritidis brain abscesses are very rare and are usually associated with immunocompromised conditions. Our patient appears to be the first reported case associated with SCD, the pathogenesis of which is unclear at present. Further clinical research is suggested in countries with a high prevalence of SCD to determine the association of SCD and the development of Salmonella brain abscesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Salmonella consists of approximately 1700 serotypes, and each serotype may cause gastroenteritis food poisonings, and generally is a self-limiting disease. Bacteremia occurs in 5-45% of the patients (7). It was reported that spread of microorganisms with bacteremia may lead to complications such as meningitis, brain abscess, septic arthritis, liver abscess, parotid abscess and muscle abscess (3, 4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella consists of approximately 1700 serotypes, and each serotype may cause gastroenteritis food poisonings, and generally is a self-limiting disease. Bacteremia occurs in 5-45% of the patients (7). It was reported that spread of microorganisms with bacteremia may lead to complications such as meningitis, brain abscess, septic arthritis, liver abscess, parotid abscess and muscle abscess (3, 4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…The recommended duration of antibiotic treatment is 4 to 6 weeks or longer, with clinical and radiological monitoring. 3,5 Conflict of interest: we have no conflict of interest.…”
mentioning
confidence: 97%
“…5 Mahapatra et al 6 in a review of cases of focal intracranial Salmonella infections in the world literature between 1884 and 2001, reviewed 80 reported cases of focal intracranial Salmonella infections, of which 22 were brain abscesses, 40 subdural empyemas and 18 were combinations of abscesses, empyemas, and epidural abscesses. 3,5,6 According to them, brain abscesses were common in adults and subdural empyemas more frequent in children. In general, their prognosis is poor with a mortality rate as high as 21-60% described in some patient series and a significant number of survivors developed permanent neurological sequelae.…”
mentioning
confidence: 99%
See 2 more Smart Citations